Value of markers of systemic inflammation for the prediction of postoperative progression in patients with pancreatic neuroendocrine tumors - Yang, Liu; Fu, Mengfei; Yu, Li; Wang, Hanyu; Chen, Xiao; Sun, Hui (Frontiers in Endocrinology, 2024)
Background: Noninvasive prognostic predictors for the rare pancreatic neuroendocrine tumors (PNETs) are lacking. We aimed to approach the prognostic value of preoperative systemic inflammatory markers in patients with PNETs.survival curve showed that the progression-free survival rate was lower in the high NLR group (P =0.004), the low LMR group (P <0.001), and the high PLR group (P =0.018). The results of multivariate Cox proportional hazards model suggested that preoperative LMR (HR =3.128, 95% CI: 1.107~8.836, P =0.031) was an independent predictor of PFS.The markers of systemic inflammation, especially LMR, can predict the postoperative progress of PNETs.